Yeast interactions in multi-starter wine fermentation. (February 2015) - Ciani, Maurizio; Comitini, Francesca
Graphical abstract: Highlights: Mixed fermentation used to improve specific traits, or to enhance the complexity of wines. Optimization of multistarter fermentation through the knowledge of yeast interactions. Yeast interactions influence metabolite production and microbial growth. Use of multistarter fermentation to control spoilage wine yeasts. Abstract : Spontaneous fermentation of grape juice is driven by a complex community of microorganisms, although diffusion of the use of selected strains of Saccharomyces cerevisiae has lead to the simplification of microbial communities in the fermentation process. More recently, there has been a growing interest towards controlled mixed fermentations that use more than one selected yeast strain. This thus aims to improve specific traits, or in general to enhance the complexity and particular characteristics of the resulting wines. In this context, yeast interactions have a fundamental role to obtain the desired product characteristics. These interactions can affect the metabolite production and/or the microbial growth. To control and optimise complex mixed fermentation, further knowledge of both of these aspects is needed.